Богдан Кістяківський. На захист права - Альчук, М.П. (Інститут держави і права ім. В.М. Корецького НАН України, 2006)
Кистяковский Богдан – известный украинский философ права. Анализируются его философско-
правовые взгляды на роль интеллигенции в жизни человека, общества. Рассматриваются проблемы правосознания и прав личности, их значение в формировании правового государства. Подчеркивается их актуальность для правотворчества и воспитания правой культуры украинского народа. Bogdan Kistyakivsky is a known Ukrainian legal philosopher. The article analyzes his legal philosophy
views on the role of intellectuals in the life of people and society. The article considers problems of law
consciousnesses and persons’ rights, their importance in the state of rule of law. The author emphasizes that
legal philosopher’s thoughts may be relevant to the present-day legislation processes and upbringing of the
legal culture in the Ukrainian society.